2007
DOI: 10.1523/jneurosci.2851-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Interactions between Fibrosarcoma Cancer Cells and Sensory Neurons Contribute to Cancer Pain

Abstract: In an experimental model of cancer pain, the hyperalgesia that occurs with osteolytic tumor growth is associated with the sensitization of nociceptors. We examined functional and molecular changes in small-diameter dorsal root ganglion (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 68 publications
8
70
0
Order By: Relevance
“…Although we cannot rule out the possibility that mechanically-insensitive nociceptors developed mechanical sensitivity as a result of tumor growth, our data suggest that mechanical hyperalgesia in this model of cancer pain may result from central sensitization. Indeed, we have shown that wide dynamic range neurons in the dorsal horn of the spinal cord exhibited enhanced responses to mechanical stimuli (Khasabov et al, 2007). Attenuation of tumor-evoked mechanical hyperalgesia by peripheral administration of WIN 55,212-2 appears to be mediated by reduced spontaneous activity in C-fiber nociceptors which may decrease the C-fiber drive to maintain the sensitization of nociceptive dorsal horn neurons, and by a decrease in responses of C-fibers evoked by mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot rule out the possibility that mechanically-insensitive nociceptors developed mechanical sensitivity as a result of tumor growth, our data suggest that mechanical hyperalgesia in this model of cancer pain may result from central sensitization. Indeed, we have shown that wide dynamic range neurons in the dorsal horn of the spinal cord exhibited enhanced responses to mechanical stimuli (Khasabov et al, 2007). Attenuation of tumor-evoked mechanical hyperalgesia by peripheral administration of WIN 55,212-2 appears to be mediated by reduced spontaneous activity in C-fiber nociceptors which may decrease the C-fiber drive to maintain the sensitization of nociceptive dorsal horn neurons, and by a decrease in responses of C-fibers evoked by mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Cultures were prepared from DRGs collected from all levels of the spinal cord as previously described [35]. Cells in the final suspension were plated at a density equivalent to ~3 DRGs/laminin-coated glass coverslip for biochemical studies.…”
Section: Methodsmentioning
confidence: 99%
“…More recent evidence supporting a key role for chemokines and their receptors in chronic pain has come from the results of experiments using several accepted models of neuropathic pain in rodents. These models include sciatic nerve transaction (54,55), partial ligation of the sciatic nerve (26,56,57), chronic constriction injury of the sciatic nerve (58)(59)(60) (61,62), and zymosan-induced inflammatory pain (58,63,64). Each of these models resulted in up-regulation of one or more chemokine receptors by DRG neurons associated with, or in close proximity to, the injury.…”
Section: Chemokines and Their Receptors In Acute And Chronic Painmentioning
confidence: 99%